Endemic plant species in the west of Hebron, Palestine - Ighbareyeh, Jehad Mahmoud Hussein; Cano-Ortiz, Ana; Cano, Eusebio (European Journal of Applied Sciences, 2021)
This research contains a study of part of the vegetation cover in the west of Hebron territories (Idna & Suba, Al-kum, Farsh Al-Hawa and Tarqumia village) in Palestine, including many different plant varieties. This area is of great local importance for plants with a good endemism rate of 13%. The aim of this study is to identify the endemic species and determine their life form and habitat. Over 200 random samples were also analysed for over 1,300 species of plants distributed in the study area, based on the Braun-Blanquet methodology for botanical analysis. During the process of studying and analysing the flora, 169 endemic plant species were recorded out of a total of 1,300 plant species and 35 family, and covering an area of about 71 Km2. According to Raunkiaer’s life form system of endemic plants, were the tree (4.73%), phanerophytes as a trees & shrubs (6.50% dominated followed by Rhamnus palaestinus Boiss., Pistacia palaestina Boiss., Ficus cariaca L., Quercus look Kotschy, Lycium schweinfurthii Dammer.; annuals or therophyte (43%) as Anthemis leucanthemifolia Boiss., Anthemis bornmuelleri Stoj. & Acht., Anthemis brachycarpa Eig., Anthemis cornucopiae Boiss., Anthemis edumea Eig., Anthemis eliezrae Eig. Tulipa boissieri Regel; geophytes (15.02%) as Asparagus palaestinus Baker, Gagea dayana Chodat & Beauverd; hemicryptophytes (14%) as Exoacantha heterophylla Labill., Onopordum telavivense Eig. and Rheum palaestinum Feinbrun; and chamaetophyte & semi shrubs (10.65%) as Phlomis brachyodon (Boiss.) Zohary; Papilionaceae, Compositae and Lamiaceae were among the wealthiest families in the current study, accounting for (12.42%), (11.83%) and (10%) of the taxa, respectively. The region study is belong to the dry, arid and semi-arid of ombrotype, and thermo-inframediterranean thermotype.